1986
DOI: 10.1177/34.3.3512692
|View full text |Cite
|
Sign up to set email alerts
|

Fluorochrome-coupled lectins reveal distinct cellular domains in human epidermis.

Abstract: The distribution of saccharide moieties in human interfollicular epidermis was studied with fluorochrome-coupled lectins. In frozen sections Concanavalin A (Con A), Lens culinaris agglutinin (LCA), Ricinus communis agglutinin I (RCAI), and wheat germ agglutinin (WGA) stained intensively both dermis and viable epidermal cell layers, whereas peanut agglutinin (PNA) bound only to living epidermal cell layers. Ulex europaeus agglutinin I (UEAI) bound to dermal endothelial cells and upper cell layers of the epiderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
2
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 30 publications
4
32
2
1
Order By: Relevance
“…Although some studies have reported that the DBA conjugates, with a nominal specificity for blood group AI, would react with endothelia in blood group A specimens (Hsu and Ree, 1983;Schaumburg-Lever et al, 19841, both our earlier studies (Virtanen et al, 1986;Hormia et al, 19881, those of others (Damjanov, 19871, Fig. 3. Reactivity of the GSA-I-B4 and SJA conjugates with human kidney specimens.…”
Section: Discussionmentioning
confidence: 77%
“…Although some studies have reported that the DBA conjugates, with a nominal specificity for blood group AI, would react with endothelia in blood group A specimens (Hsu and Ree, 1983;Schaumburg-Lever et al, 19841, both our earlier studies (Virtanen et al, 1986;Hormia et al, 19881, those of others (Damjanov, 19871, Fig. 3. Reactivity of the GSA-I-B4 and SJA conjugates with human kidney specimens.…”
Section: Discussionmentioning
confidence: 77%
“…Glycoconjugates are generally regarded as playing important roles in, e.g., the morphogenesis of organs, transformation of cells (5,19), and adhesion of ceh (3,29). VariouS lectin conjugates such as H'K-kctin (6,7,33,34), peroxrdase-lectin (23,26), biotinylated lectin (8,15,35), or colloid?l gold-kctin (20,21) h2R been developed U, demonstrate the localizltion o f glycoconjugates histochemically. Lectin histochemistry has been employed to characterize the glycoconjugates in adult kidney tissues at both light and electron microscopic levels.…”
Section: Introductionmentioning
confidence: 99%
“…Lektinler karbonhidrat bağlayan proteinlerdir, en az iki şeker bağlama bölgesi içerirler, enzimatik aktivite göstermezler ve insan, bakteri veya bitki kaynaklı olabilirler Genellikle çeşitli epitellerdeki glikokonjugat dağılımları 8,9 , gelişim ve farklılaşma üzerine çalışmalarda kullanılırlar 10 . Lektinlerle ilgili çok fazla sayıda çalışma olmasına rağmen diş eti dokusu, diyabet ve lektinler arasındaki ilişkiler hakkında çalışma yok denecek kadar azdır, özellikle yapılan literatür araştırmalarında diyabetik hastaların diş eti dokusunun lektinlerle olan ilişkilerine dair bir çalışmaya rastlanmamıştır.…”
Section: Discussionunclassified